PROCESSIONS AND THEIR CHANTS IN THE OLD HISPANIC LITURGY. (2020) - ANDRÉS FERNÁNDEZ, DAVID; GUTIÉRREZ, CARMEN JULIA; HORNBY, EMMA; ROJO CARRILLO, RAQUEL
Abstract : Much is known about processions within the Roman liturgy, but the processions of the Old Hispanic rite practiced in most of Christian Iberia until ca. 1080 have not been studied. Explicit evidence about Old Hispanic processional characteristics and liturgical contexts is preserved in manuscript rubrics. Processions happened around or during Mass (for example, on Palm Sunday), at the end of Vespers or Matutinum (for example, the consecration of a basilica), or outside the usual daily liturgy (for example, votive ordos). We have collated all of the extant Old Hispanic rubrics pertaining to liturgical movement. Some of these unquestionably refer to processions, while others describe ceremonies that might better be described more informally as "liturgy in motion." We focus primarily on the processional rubrics, while also engaging with other liturgical movement. We identify the chant genres associated with processions and outline the processional practices attested in the rubrics.